2001
DOI: 10.1161/hq1201.099433
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Constitutes an Independent Predictor of Advanced Carotid Plaques in Dyslipidemic Subjects

Abstract: Abstract-Inflammation plays a key role in the physiopathology of atherosclerosis. C-reactive protein (CRP) has been found to predict cardiac events in healthy subjects and in patients with coronary heart disease. However, the relationship between CRP and subclinical atherosclerosis is not well established. We examined the potential relationship between CRP and common carotid artery intima-media thickness and carotid plaques in dyslipidemic subjects. Dyslipidemic patients (nϭ1051) were recruited for the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
6
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 66 publications
7
79
6
1
Order By: Relevance
“…In contrast, our study showed that the CRP level is not associated with the development of carotid plaque or progression of the C-IMT. This finding may be attributed to the relatively low levels of CRP observed in this study compared to other studies 34,35) , likely reflecting a minimal contribution to plaque formation. However, risk factors for the progression of C-IMT are inconsistent and differ according to sex, depending on the study participants 36,37) .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast, our study showed that the CRP level is not associated with the development of carotid plaque or progression of the C-IMT. This finding may be attributed to the relatively low levels of CRP observed in this study compared to other studies 34,35) , likely reflecting a minimal contribution to plaque formation. However, risk factors for the progression of C-IMT are inconsistent and differ according to sex, depending on the study participants 36,37) .…”
Section: Discussioncontrasting
confidence: 61%
“…An increased level of CRP also reflects low-grade inflammation and is associated with carotid atherosclerosis, although there is a gender difference 34,35) . In contrast, our study showed that the CRP level is not associated with the development of carotid plaque or progression of the C-IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present results are in line with numerous former crosssectional studies. [37][38][39][40] Despite major advances in treatment of stroke, early identification and prevention of incident events remain crucial, because more than two thirds of all strokes occur without prior symptoms. Recently, Bertges et al 2 demonstrated that progression of carotid artery disease as indicated by duplex ultrasound investigations translates clinically into a substantially increased risk for ipsilateral neurological events.…”
Section: Discussionmentioning
confidence: 99%
“…31 High plasma levels of hs-CRP may be associated with a higher incidence of late adverse events after successful coronary stenting. 32 Elevated hs-CRP constitutes an independent predictor of advanced carotid plaques in dyslipidemic subjects, 33 and early-onset carotid atherosclerosis is associated with increased intima-media thickness and elevated serum levels of inflammatory markers. 34 A graded association between hs-CRP and carotid atherosclerosis has been demonstrated in women but not in men.…”
Section: High-sensitivity C-reactive Protein and Other Inflammatory Mmentioning
confidence: 99%